Planning support science: Developments and challenges. (October 2020) - Geertman, Stan; Stillwell, John
In this paper, we provide an update of recent developments and forthcoming challenges in the field of planning support systems, following earlier reviews in 2003 and 2009. The rationale for this update is the rapid development of information and communication technologies and their impact on planning support systems. After a brief retrospective assessment of past planning support system developments, the paper presents a synthesis of the experiences and views of a worldwide sample of invited planning support system experts, whose innovative contributions comprise a new Handbook of Planning Support Science. The developments documented by the experts together substantiate our impression that a fundamental transformation is taking place – a paradigm shift – wherein the field of planning support systems is maturing into a planning support science . From this perspective, it is expected that planning support systems will become indispensable instruments in the planning process in the not too distant future. The signs of this maturation are already visible in research, education and practice.